Subjective Outcome Evaluation of the Project P.A.T.H.S.: Findings Based on the Perspective of the Program Implementers - Daniel T. L. Shek; Andrew M. H. Siu; Tak Yan Lee (The Scientific World Journal)
A total of 52 schools (n = 8679 students) participated in the experimental implementation phase of the Project P.A.T.H.S. (Positive Adolescent Training through Holistic Social Programmes). After completion of the Tier 1 Program, 344 instructors completed the Subjective Outcome Evaluation Form (Form B) to assess their views of the program, instructors, and perceived effectiveness of the program. Based on the consolidated reports submitted by the schools to the funding body, the research team aggregated the consolidated data to form a “reconstructed” overall profile on the perceptions of the program implementers. Results showed that high proportions of the workers had positive perceptions of the program and their own performance, and roughly 90% of the workers regarded the program as helpful to the program participants. The present study provides additional support for the effectiveness of the Tier 1 Program of the P.A.T.H.S. Project in Hong Kong.